L’influence normative de l’OCDE sur la Directive-cadre européenne sur l’eau (DCE) - Delphine Loupsans (VertigO)
The European Water Framework Directive (WFD) binds European Union countries to a policy of water quality and aquatic environment restoration by 2015. It breaks new ground by defining a European framework for water policy by instituting a comprehensive protection of the resource and setting ambitious environmental goals, with an obligation of results. However, the format and requirements arising from the text are not the only innovation of the WFD. This article demonstrates that even if the text remains related to previous community legislation, it is also inspired by OECD-developed knowledge, sometimes in areas unrelated to aquatic environments management. Therefore, this article identifies the influence upstream by OECD on the development process of the WFD to better understand its political orientation.